Series hybrid electronic vehicle cost-effective power train components development - Ramasamy, D. (2008)
Hybrid electric vehicles (HEV) have been sought for its clean and frugal operation. It was also seen as the next replacement for petrol and diesel fuel vehicles, bridging the gap between now and the future of zero emission electric vehicles. HEVs used both engines and electric motor, creating a great symbiosis that benefits fuel consumption as well as exhaust emission. These HEVs have long been utilized since year 2000 in Japan, United States, United Kingdom and even Singapore. These HEVs however are parallel HEVs, meaning the engines are powering the vehicles parallel with its electric motor. Either one of the engine or electric motor can function at once or both together, depending on situation of load requirement and running mode. Controlling the system is complicated but integrating the system itself is simple. The biggest motivation to develop this configuration would be its flexibility and efficiency.